Building Beyond The Mediterranean Studying The Archives of European Businesses (1860-1970) - Piaton, Claudine; Godoli, Ezio; Peyceré, David (InVisu, 2012)
Suez, Abu Simbel, Cairo, Algiers, Casablanca, Istanbul... This work of pioneering research by architectural historians and archivists gives us access to an exceptional field of European cultural heritage: the records of buildings and public works contractors active on the southern shores of the Mediterranean between 1860 and 1970. It covers all the construction trades, from steel or reinforced concrete bridges and dams, housing for laborers and expats, and public buildings, but also furniture, decoration, and studio crafts. All of these projects attest to the intensity of the human, technical, and artistic exchanges occurring in this period between Europe and the south-eastern Mediterranean rim. This book is illustrated with over 200 rare drawings and photographs drawn directly from the builders'archives, including old photos intended to promote the contractor's business, construction site photos, architects' plans, sketches, and notes documenting technical innovations, and vintage advertising brochures, etc. This book is the product of the transnational cooperation project "ARCHING: ARChives d'INGénierie européennes" (2010-2012) carried out as part of the European Commission Culture Programme 2007-2013, in conjunction with five institutions: the Ecomusée du Bois-du-Luc (Belgium), the Cité de l'architecture et du patrimoine (France), InVisu (CNRS-INHA) (France), the Dipartimento di Architettura disegno-storia-progetto of the University of Florence (Italy) and the Archmuseum (Turkey).